Analysis of resistance popular cryptosystems against quantum cryptanalysis based on Grover's algorithm - Горбенко, Юрій Іванович; Ганзя, Роман Сергійович (Ukrainian Information Security Research Journal, 2014)
The problem of resistance the popular cryptosystemsagainst quantum cryptanalysis is an urgent and importanttask, given the pace of development of quantum technologies.Resistance of all modern cryptosystems based on thecomplexity of solving certain mathematical problems. Suchmathematical problems tend to have exponential complexityor subexponential solutions, using quantum algorithmsthat have been proposed Shore and Grover the complexityof solving such problems is reduced to a polynomial. SoShor's algorithm reduces the complexity of cryptanalysistransformations in the ring, field and in the group of pointson elliptic curves. The article describes the using ofGrover's algorithm for cryptanalysis popular symmetricblock ciphers. The methods of quantum cryptosystemscryptanalysis NTRU, based on a combination of classicalattacks and meeting in the middle of Grover's quantumalgorithm. In this paper we proposed our estimates of resistanceof block popular ciphers and cryptosystemsNTRU with different sizes of the quantum system-wideparameters against cryptanalysis based on the use ofGrover's quantum algorithm. The article also shows thecharacteristics that must have a quantum computer forsuccessful cryptanalysis of certain cryptosystems.